CAMPURAN SABUT KELAPA DAN AMPAS TAHU UNTUK MEDIA TANAM PERKECAMBAHAN UNTUK MENDUKUNG PERTANIAN ORGANIK - Ramadhani, Alvianty; Puspitawati, Mutiara Dewi (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2023)
Coconut husk is a waste from coconut plantation production and tofu waste is solid waste from tofu production. One problem and coconut husk is the tannin content that can inhibit plant growth and the low nutrient content of coconut coir. This study aims to determine the effectiveness of a mixture of coconut husk and tofu waste as a planting medium for germinating green beans, bok choy, and red chili in supporting organic farming. This research was carried out in Kaliabang Tengah District, North Bekasi District. From October 2021 until February 2022. The study used a factorial Randomized Complete Block Design (RCBD) with one treatment factor. The first factor was planting media with M0= soil treatment, M1= coconut husk + tofu waste, M2 = coconut husk soaked in alum+ tofu waste, and M3= coconut husk soaked in detergent+ tofu waste. This study uses different plants with different seed sizes, green beans, bok choy, and red chili. The results of this study indicate that a good and effective planting medium for germination, germination age, and plant height is coconut husk soaked with alum + tofu waste. The use of growing media for coconut husk and tofu waste can interpret soil planting media in bean plants and plan height parameters on bok choy plants and as alternative media to replace soil planting media in supporting organic farming.